The effects of a humanized recombinant anti-cocaine monoclonal antibody on the disposition of cocaethylene in mice - Wetzel, Hanna N. (Int Immunopharmacol, 2014)
The chimeric human/mouse anti-cocaine monoclonal antibody (mAb) 2E2 and its further humanized variant h2E2 have been reported to sequester a significant portion of cocaine in plasma and decrease cocaine concentrations in the brain in mice and rats. However, many cocaine users co-abuse alcohol, leading to the formation of the centrally active metabolite cocaethylene. This potentially compromises the efficacy of a cocaine-specific immunotherapy. Because h2E2 has high affinity for cocaethylene as well as cocaine, the ability of h2E2 to prevent cocaethylene entry into the brain was investigated. Mice were infused with h2E2 (1.6 µmol/kg i.v.) or vehicle and after one hour were injected with cocaethylene fumarate (1.2 µmol/kg i.v.). At times from 45 seconds to 60 minutes, brain and plasma were collected and cocaethylene concentrations were measured using GC/MS. In control mice, a two-compartment pharmacokinetic model generated values for cocaethylene distribution and terminal elimination half-lives of 0.5 and 8.1 min respectively. Initial plasma cocaethylene concentrations increased 13-fold from controls in the presence of h2E2. In brain, h2E2 produced a 92% decrease in the area under the time-concentration curve for cocaethylene. The pharmacokinetics of h2E2 were also characterized in detail. A three-compartment model resolved an initial distribution half-life of 4.4 minutes and a second distribution half-life of 4.2 hours, and a terminal elimination half-life of 7.8 days. The ability of h2E2 to protect the brain from both cocaine and cocaethylene predicts that the clinical efficacy of h2E2 will be retained in cocaine users who co-abuse alcohol.